AN ANALYSIS OF THE INSTRUCTIONS IN BAHASA INGGRIS TEXTBOOK FOR GRADE 10th STUDENTS PUBLISHED BY THE INDONESIAN MINISTRY OF EDUCATION AND CULTURE - Selvi Maharani; An Fauzia Rozani Syafei; Sitti Fatimah (Journal of English Language Teaching, 2018)
AbstractThis research is a descriptive research conducted to find out the quality of the Instructions in Bahasa Inggris textbook for 10th Grade Students Published by the Indonesian Ministry of Education and Culture in term of instruction used. The instrument of this research was an analysis format used by the researcher as the guidelines to eanalyze the textbook. The analysis format contained of instruction categories that consists of three indicators as the criteria of good instructions. After the analysis, it was found out the quality of the Instructions in Bahasa Inggris textbook for 10th Grade Students Published by the Indonesian Ministry of Education and Culture in term of instruction used is not qualified as the good textbook because only one criterion that fulfils the good quality of instructions used; instruction that permit silent period were 93.3%. However, the other criteria could not be categorized into good instruction since they were only found 54.4% instructions of building critical thinking, and instructions that are followed by example were 45.7%. It means that only instructions that permit silent period that fulfils the criteria of good textbook, while for building critical thinking and followed by example are only average.Key words: Teaching Materials, Materials analysis, Instruction, HOT (Higher Order Thinking), Bloom’s Taxonomy, the Silent Period